« Somnambulisme », ou l’après-coup de la métaphore - Marc Amfreville (Transatlantica)
This essay aims to show that “Somnambulism,” a short story by Charles Brockden Brown published in 1799 foreshadows several Freudian tenets that allow, in turn, to fully measure the symbolic purport of this fiction. Reading thus becomes bidirectional, obeying the very principle of Nachträglichkeit (deferment or belatedness). The representation of what the eighteenth century viewed as a serious mental illness for all its poetical associations ends up shattering any chronological conception of knowledge, and thus confirms the commonness of literary and Freudian intuitions on the Unconscious, but also sheds light on doubling, splitting and ambivalence.